Observational Study of "Chai Hu Jia Long Gu Mu Li Tang" (Bupleurum adnd Dragon Bone) on Menopausal Syndrome - Teo, Elsie Sin May (2015)
Introduction. “Menopause” denotes the final cessation of menstruation, resulting from loss of ovarian follicular function, usually due to aging. Symptoms that have been shown to be associated with estrogen deficiency after the menopause are hot flushes and night sweats, insomnia and vaginal dryness. Vasomotor episodes with hot flushes and night sweating are the most prevalent complaints related to menopause. Hormone therapy with estrogen is considered as the most effective treatment in treating symptoms of menopause. However, recent research show that long term use of estrogen increases the risk of serious adverse effects, so, prompting sufferers to seek other therapies.